2010
DOI: 10.1164/rccm.200909-1396oc
|View full text |Cite
|
Sign up to set email alerts
|

The Metalloprotease-Disintegrin ADAM8 Is Essential for the Development of Experimental Asthma

Abstract: The results show that ADAM8 plays a proinflammatory role in airway inflammation. The milder disease outcome in the absence of ADAM8 suggests that this protein might be an interesting new target in treatment of this, and potentially other, inflammatory diseases in which recruitment of inflammatory cells is an essential part of pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 50 publications
7
56
1
Order By: Relevance
“…For instance, Mmp8 2/2 mice display higher neutrophilic inflammation, being the consequence of a lack of LIX processing that delays apoptosis of these cells (12,(43)(44)(45). Adam8 2/2 mice display less eosinophilic inflammation (22) and impaired dendritic cell recruitment (15,22). Adamts12 deletion leads to hyperresponsiveness associated with enhanced eosinophil and mast cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Mmp8 2/2 mice display higher neutrophilic inflammation, being the consequence of a lack of LIX processing that delays apoptosis of these cells (12,(43)(44)(45). Adam8 2/2 mice display less eosinophilic inflammation (22) and impaired dendritic cell recruitment (15,22). Adamts12 deletion leads to hyperresponsiveness associated with enhanced eosinophil and mast cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…These membraneassociated enzymes bear multifunctional domains, including a catalytic domain, a disintegrin domain, and a cysteine-rich domain (18). Their expression is increased in asthmatic patients (19,20) and in murine asthma models (21,22). ADAM33 is the first asthma susceptibility gene that has been recognized by positional cloning (16).…”
mentioning
confidence: 99%
“…In addition, we demonstrated that ORMDL3 selectively regulates activation of the ER localized transcription factor ATF6α signaling branch, a pathway we have demonstrated in human lung epithelial cells is linked to SERCA-2b, which is implicated in airway remodeling in asthma (24). Finally, our studies demonstrate that ORMDL3 activates several metalloprotease, chemokine, and OAS-regulated genes, several of whom have also been implicated in the pathogenesis of asthma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Overall, these studies provide evidence for a mechanism to link an ER localized protein such as ORMDL3 to the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 72%
“…The importance of these ORMDL3-regulated genes to asthma is suggested from studies demonstrating increased expression of many of these mediators in the airways of human asthmatics (MMP-9, ADAM-8, CCL-20, CXCL-10, IL-8) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), induction of these mediators by allergen inhalation in asthmatics (MMP-9, CCL-20, CXCL-10) (7,12,19), and inhibition of asthma outcomes in mice deficient in these genes (MMP-9, ADAM-8, CXCL-10) (8,9,11,20,21). In addition to the important role of CCL-20 on T-cell recruitment (12), and epithelial mucus production (14), in mouse models of asthma, there is a critical link between CCL-20 and TRAIL for Th2 cell activation and allergic airway inflammation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the ADAM family function as sheddases by cleaving type I and type II integral single membrane proteins to generate soluble forms of these proteins (5) and have been found to be involved in the etiologies of a variety of diseases and conditions (6)(7)(8). Members of the ADAM family can degrade the extracellular matrix (ECM) and control cell adhesion and movement through regulation of intercellular adhesion, protease activity and cell activities that are closely related to the metastasis of human tumors (9,10).…”
Section: Introductionmentioning
confidence: 99%